IS IT WHERE YOU GO OR WHAT YOU STUDY? THE RELATIVE INFLUENCE OF COLLEGE SELECTIVITY AND COLLEGE MAJOR ON EARNINGS. - Eide, Eric R.; Hilmer, Michael J.; Showalter, Mark H. (Contemporary Economic Policy, 2016)
All college students must decide where to attend college and what major to study. We estimate how earnings by college major differ at different college selectivity types. We find major-specific earnings vary markedly by college selectivity, with the strongest differences among business majors and the weakest differences among science majors. We also find that when comparing earnings of graduates from top colleges to middle or bottom ranked colleges, the distribution of students across majors can be as important as earnings differences by major in accounting for college selectivity earnings gaps.